Presence and Transfiguration in the Christian East Worship Image - Moya Ruiz, Albert (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2019)
Presence and transfiguration constitute two key concepts of the icon’s theology in Christian East. The different functions that Orient attributes to Christian worship image can be established from these two concepts. Both notions are linked to Dogmatic Theology and are framed in the mystery of the Incarnation of Christ. They condense at the same time the teachings and demands of the theological tradition of the Church Fathers, which is based on the logic of deification and also on the ontological foundation of the cult image. This statement is established on the anamnesis and the presence of the prototype in the image.
Keywords: icon; presence; transfiguration; beauty; art; symbol